A resource generator methodology for hotels - Maria Angeles Revilla Camacho; Manuel Rey-Moreno; Ángeles Gallego; Cristóbal Casanueva (Journal of Innovation & Knowledge (JIK), 2019)
Hotel firms can enhance their performance by accessing external resources through their inter-personal and inter-organizational ties. However, neither has a repertory been compiled of relevant external resources in the sector, nor are appropriate diagnostic and analytical tools available to improve the way these resources may be used. The hotel resource generator is an instrument adapted from the field of sociology that is used here to measure access to those network resources. It is presented in this study as a tool to measure the external resources that condition the performance of hotel firms and is tested on a sample of hotels from Andalusia (Spain).
Keywords: L83; M10; 650; Hotel resources; Network resources; Resource generator; Social capital